Deforestation as a Cause of Increased Surface Runoff in the Catchment: Remote Sensing and SWAT Approach—A Case Study of Southern Serbia - Potić, Ivan; Mihajlović, Ljiljana M.; Šimunić, Vanja; Ćurčić, Nina B.; Milinčić, Miroljub (Frontiers in Environmental Science, 2022)
In the past two decades, the South part of Serbia has been affected by exploitive and illegal logging. As this trend is not decreasing to this day, there is a need to determine the area where this logging occurred precisely. The consequences of these actions are tremendous, causing the forest owners' financial loss (regardless of whether it is private or state property) and a negative impact on the environment. Significant environmental and forest management problems deriving from these actions are erosion increase and more frequent torrential floods occurrence in the catchment. Since it is difficult to update the national forest inventories in remote areas, remote sensing techniques using different satellite imagery types can provide up-to-date data. The initial analysis that employed NDVI (created using Landsat 7 and Landsat 8 imagery) indicates massive deforestation in the research area between 1999 and 2021. Headwaters of the Štavska river catchment is selected as the research area to determine the amount of erosion in two periods — before and after deforestation occurred. Change in land cover (LC) is presented with two LC maps created applying supervised classification to Landsat 7 imagery from 1999 as a pre-deforestation LC state and Landsat 8 imagery acquired in 2021 as the current LC state. The erosion in the catchment for both periods is determined using the Soil and Water Assessment Tool (SWAT). The analysis results show the erosion change incurred as a deforestation effect in the river catchment. With the data obtained by remote sensing and SWAT analysis, it is possible to track changes in the area and acquire essential data, making the right and fast decisions to protect the natural resources economy and make sustainable development possible in this impoverished region.